In situ formation of large-scale Ag/AgCl nanoparticles on layered titanate honeycomb via gas phase reaction for solar light degradation - Lau, Teck Hua. (2011)
Conventional TiO2 - based photocatalyst possesses excellent stabilities and activities, but it has a large band gap (~ 3.2 eV) and requires near ultraviolet (UV) irradiation for photocatalytic application thereby limiting its practical usage under solar light. Therefore, efforts have been devoted to synthesize a high efficient photocatalyst that is capable of using visible light under solar irradiation. In this report, large scale and homogeneously distributed AgCl nanoparticles (NPs) were grown onto the titanate honeycomb (THC) thin film which composed of long twisting one dimension (1D) titanate nanowires. This THC thin film was synthesized via a simple alkaline hydrothermal method with relatively low alkaline NaOH (1 M) and a short duration (6 hours). Subsequently, a facile solution ion-exchange method was deployed to remove the Na+ ions in the inter-layer of the titanate by soaking the THC thin film in HNO3 and AgNO3 solution separately. Therefore, the Na+ ions will be replaced by H+ then by Ag+ ions without changing the morphology or crystal structure of the thin film. Follow on, the obtained silver THC thin film was exposed to HCl gas to readily form AgCl NPs onto the THC thin film. The Ag+ ions in the surface region of the AgCl NPs can then be partially reduced to form Ag0 metal atoms under xenon light illumination to form Ag/AgCl/THC photocatalyst. Thus, this as-synthesized photocatalyst exhibits plasmonic resonance due to the Ag atoms, which will amplify the absorption of visible light and enhance the photocatalytic activity for the degradation of phenol in water. The as-synthesized Ag/AgCl/THC thin film was characterized by XRD, XPS, SEM and TEM. Lastly, the Ag/AgCl/THC exhibited excellent photocatalytic activity and stability for the degradation of phenol based on the high performance liquid chromatography (HPLC) analysis.